Evaluation of a promising tomato line (Solanum lycopersicum) derived from mutation breeding - Enik Nurlaili Afifah; Rudi Hari Murti; Aditya Wahyudhi (Society for Indonesian Biodiversity, 2021)
Abstract. Afifah EN, Murti RH, Wahyudhi A. 2021. Evaluation of a promising tomato line (Solanum lycopersicum) derived from mutation breeding. Biodiversitas 22: 1863-1868. Tomato (Solanum lycopersicum L.) is a common crop that is widely cultivated and consumed around the world. Demand for tomatoes has increased along with the growth of the human population. Therefore, tomato production has to be continuously developed to meet the ever-rising global demand. Mutation breeding is one of the strategies applied to improve plant yield and quality. This study evaluated a promising mutant breeding line called G6 and compared it to existing varieties. G6 (mutant line), Ratna, Tora, and Intan (commercial varieties) were used as materials and were evaluated for their qualitative and quantitative traits. Overall, G6 showed a slightly flattened fruit shape similar to Ratna. It also had the highest value of locules, long shelf life, and the number of bunches per plant compared to the existing varieties (Ratna, Intan, and Tora). The number of locules is assumed to be linked to fruit size and dimension. Long shelf life is one of the preferred qualities of both consumers and farmers, as it could prevent overmature and rotten tomato fruit during transportation. G6 differed from commercial varieties (Intan, Ratna, and Tora) in terms of the number of locules, shelf life, and the number of bunches per plant.